Effectiveness of Diff erent Cryopreservation Methods of Tomato Meristems (Lycopersicon esculentum Mill.) - Shevchenko, Nadiya O.; Mozgovska, Anna V.; ÐœÑ–roshnychenkÐ¾, Tatiana M.; Ivchenko, Tatiana V.; Bashtan, Nataliya Ðž. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 160.